Evaluation of Business Strategy and Performance in Chemical Companies in the Micro Business Category - Marlitta Stefia, Cheryl (Journal of World Science, 2022)
Micro, small and medium scale industries are one of the pillars of the Indonesian economy. It is proven that during the pandemic, Indonesia can survive the threat of a recession in 2020, not spared from the contribution of the domestic consumption sector, by also taking advantage of the circular economy. Although the turnover of industries engaged in services has decreased, the company can use the pandemic period to increase the capacity of human resources. In the future when the economy improves, the company is ready to compete fairly in the market. Common problems faced by micro, small and medium scale industries are limited human resource capacity and lack of understanding of business fundamentals. This can be concluded from the stagnant performance of micro business. This research was conducted at Isnen Laboratorium. The purpose of this research is to improve business efficiency performance. At the end of the research period, it is hoped that there will be an overhaul of the 4 business pillars so that Isnen Lab will develop optimally.